Evaluation of an evidence-based practice mentorship programme in a paediatric quaternary care setting. (March 2021) - Schuler, Ethan; Mott, Sandra; Forbes, Peter W; Schmid, Alexis; Atkinson, Carole; DeGrazia, Michele
Background: Evidence-based practice (EBP) is essential for clinical decision-making, improving care, reducing costs and achieving optimal patient outcomes. The Evidence-based Practice Mentorship Program (EBPMP) is a flexible, self-directed programme whereby participants carry out EBP projects guided by expert mentors. Aims: To evaluate EBPMP effectiveness and participant experience. Methods: To evaluate effectiveness, as measured by changes in EBP value, knowledge and implementation, participants completed pre- and post-EBPMP Quick-EBP-Value, Implementation and Knowledge (VIK) surveys. To understand participants' experiences individual and group interviews were conducted at the end of the programme and analysed using qualitative content analysis. Results: Most participants were over 50 years old, Caucasian, inpatient staff nurses, baccalaureate prepared, with over 11 years' experience. Statistically significant improvements were observed in the post Quick-EBP-VIK knowledge and implementation domains. Individual and group participant interviews revealed four categories of importance to the experience: 1. perceived benefits of EBP, 2. time as a barrier to EBP, 3. desire for more cohort interaction and 4. positive mentee–mentor experience. Conclusions: EBPMP can improve participants' knowledge and implementation of EBP in an environment that values EBP; however, opportunities exist to implement programme modifications that address barriers identified by participants including project time and increased participant interactions.